2014 IEEE 8th Sensor Array and Multichannel Signal Processing Workshop (SAM) 2014
DOI: 10.1109/sam.2014.6882417
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis for sparse based biased estimator: Application to line spectra analysis

Abstract: Abstract-Dictionary based sparse estimators are based on the matching of continuous parameters of interest to a discretized sampling grid. Generally, the parameters of interest do not lie on this grid and there exists an estimator bias even at high Signal to Noise Ratio (SNR). This is the off-grid problem. In this work, we propose and study analytical expressions of the Bayesian Mean Square Error (BMSE) of dictionary based biased estimators at high SNR. We also show that this class of estimators is efficient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…On Fig. 2, it is compared the trace of expressions (7) and (15) obtained thanks to 2000 Monte-Carlo trials to the expressions (20) and (19) obtained under the assumption of low noise variance. We can verify the good agreement of our approximations in the low noise variance regime.…”
Section: Numerical Illustrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…On Fig. 2, it is compared the trace of expressions (7) and (15) obtained thanks to 2000 Monte-Carlo trials to the expressions (20) and (19) obtained under the assumption of low noise variance. We can verify the good agreement of our approximations in the low noise variance regime.…”
Section: Numerical Illustrationsmentioning
confidence: 99%
“…In this case, the continuous estimation parameters cannot match with high probability the pre-fixed discretization of the parameter set. Consider a redundant dictionary obtained from the prefixed discretization: as the parameters of interest do not belong to the grid, it appears a "quantization error"-type [7]. To take into account this effect the measurement vector, denoted bỹ y, is given by a linear combination of few vectors extracted from the initial dictionary corrupted by an additive perturbation while the initial dictionary is known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is a severe drawback in realword operational context. This non-ideal scenario has been often observed in practice [16]- [19] and the exact sparse recovery guarantees for the estimation of a signal corrupted by a BM has been studied in [20]. In particular, in a Tx (Transmit)-Rx (Receipt) context, the Rx is usually unaware (partially or not) of the true dictionary used at the Tx.…”
Section: Introductionmentioning
confidence: 98%
“…mismatch at the estimation step. The effect of dictionary mismatch has been studied in [11], [12], it has been shown that even for a small mismatch error, the accuracy of the amplitude estimation is drastically limited even for a low noise variance and a perfectly estimated support [13].…”
Section: Introductionmentioning
confidence: 99%